Unilateral Brodie bite correction in a growing patient using palatal and buccal miniscrews: A case report - Gaddam Raj; Weir Tony; Freer Elissa (Sciendo, 2021)
This case report describes a 13-year-old Caucasian male who presented with a Class I dental relationship on a mild Class II skeletal base and an associated unilateral Brodie bite on the right side but an ideal anterior overjet and overbite. The posterior teeth in the first quadrant had supra-erupted due to a lack of opposing occlusion. The treatment comprised two phases, the first of which involved miniscrew-based intrusion of the maxillary right buccal teeth followed by non-extraction, full upper and lower pre-adjusted edgewise appliances during a second phase. A satisfactory occlusal result was achieved in 24 months.